2020
DOI: 10.1186/s13287-020-01777-6
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from adipose-derived stem cells ameliorate ultraviolet B-induced skin photoaging by attenuating reactive oxygen species production and inflammation

Abstract: Background: Large numbers of adipose-derived stem cells (ADSCs) are easily obtained and have been demonstrated to protect against ultraviolet B (UVB)-induced skin photoaging. Extracellular vesicles (EVs) exhibit some of the same effects as the cells from which they originate and have many advantages over stem cells. In particular, their application circumvents many safety concerns associated with cell therapy. Thus, as a cell-free agent, adipose-derived stem cell extracellular vesicles (ADSC-EVs) have anti-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 49 publications
4
68
0
Order By: Relevance
“…When the ADSCs‐EVs were injected into the UV‐induced photoaging mice weekly for 8 weeks, the wrinkles score was reduced significantly; a decrease in epidermal thickness and an increase in dermal thickness were also observed. In addition, the results supported that ADSCs‐EVs treatment was beneficial to collagen regeneration in vivo 27 …”
Section: Discussionsupporting
confidence: 54%
“…When the ADSCs‐EVs were injected into the UV‐induced photoaging mice weekly for 8 weeks, the wrinkles score was reduced significantly; a decrease in epidermal thickness and an increase in dermal thickness were also observed. In addition, the results supported that ADSCs‐EVs treatment was beneficial to collagen regeneration in vivo 27 …”
Section: Discussionsupporting
confidence: 54%
“…Another way to use AD-MSCs in antiaging therapy, in a “cell-free” method of treatment, is by using extracellular vesicles (EVs), which have several advantages over stem cells and their safety issues. Adipose-derived mesenchymal stem cells extracellular vesicles (AD-MSCs-EVs) have anti-photoaging potential and were analyzed as subcutaneous injections in photoaged mice models [ 112 ]. The treatment resulted in a decrease in skin wrinkles and promotion of epidermal cell proliferation.…”
Section: Applications Of Mesenchymal Stem Cells In Skin Rejuvenatimentioning
confidence: 99%
“…UV light damage is one of the most harmful environmental factors that accelerate aging. Therefore, reports have suggested that EVs from adipose-derived stem cell have anti-photoaging potential (59,60). Together, these studies suggest that EVs from stem cell could be good candidates for therapeutic strategies against aging.…”
Section: Discussionmentioning
confidence: 91%